Machinability of Zirconia Toughened Mica Glass Ceramics for Dental Restorations - Gali, Sivaranjani; Chiru, Suresh (Brazilian Dental Science, 2020)
Objective: For a dental material to be machinable for CAD/CAM technology, it must offer convenient machining, under a given set of cutting conditions. Quantitative evaluation of machinability has been assessed in literature through various parameters such as tool wear, penetration rates, surface roughness, cutting force and power. A machinable ceramic will typically demonstrate a higher tool penetration rate with signs of reduced diamond tool wear and edge chipping. The purpose of this in vitro study was to evaluate the feasibility of machining an experimental ceramic, 20 wt.% zirconia reinforced mica glass ceramics (G20Z) for indirect dental restorations and compare the tool penetration rates of G20Z to commercially available dental ceramics, Presintered Zirconia (PSZ) and IPS emax CAD. Material and Methods: Precursors of base glass (SiO2 -Al2O3 -K2O -MgO-B2O3 -F) were melted at 15000C for 2 h in a platinum crucible and quenched in deionised water. The glass frit was ball milled with 20 wt. % YSZ (G20Z) and subject to two stage heat treatment in a muffle furnace. Specimens of G20Z (12 X 2 mm) were evaluated for their feasibility of machining under varying spindle speed, depth of cut, and feed rates. Influence of depth of cut, spindle speed and feed rate (vc=8000-16000 rpm, d=0.4-0.8 mm, f=0.1- 0.3 mm/tooth) on cutting forces, material response, surface roughness and tool wear were investigated. Tool penetration rates, tool wear and margin chipping were also evaluated and compared with Pre-sintered Zirconia (PSZ) and e.max CAD in a custom dental milling surveyor at 30,000 rpm with a load of 0.98 N under water lubrication for 6 min. Tool penetration rates were calculated as the ratio of length of cut and milling time with a measuring microscope and scanning electron microscope was used for tool wear and edge chipping. ANOVA and Tukey Kramer tests were used for statistically comparing the means of each group. Results: Spindle speed and feed rate play a significant role in influencing surface roughness, thrust force, cutting forces and tool wear. Penetration rates of G20Z (0.32 ±0.12 mm/min) was significantly greater than PSZ (0.26 ±0.06 mm/min) and IPS e.max CAD (0.21 ±0.05 mm/min). SEM observations reveal tool abrasion and edge chipping regardless of the ceramic type. Conclusion: High spindle speeds delivers low cutting forces with an average surface roughness of 1.61 µm, with abrasive wear of the tool insert and brittle fracture of zirconia mica glass ceramic composites. G20Z with its machinable nature demonstrates greater tool penetration rates than PSZ and IPS e.max CAD. Tool wear and edge chipping is seen in all the investigated ceramics. Keywords Machinability, Dental Ceramics, Mica Glass-Ceramics, Dental Zirconia, Tool penetration rates.